In higher education (he) and the formation of special free academic zones in Malaysia - Ngô, Tự Lập (International school. Vietnam national university, Hanoi, 2020)
A Joint-Program is usually seen only as a mode of education technology transfer or international education business. The aim of this paper is to show that in the special historical context of Malaysia during the last decades of the 20th century, it could have deep social-political and cultural consequences, playing a role similar to that of the Special Free Economic Zones. In other words, JPs are intrinsically Special Free Academic Zones6.